ANTIMALARIAL MEDICINAL PLANTS USED BY TRADITIONAL HEALERS IN BENGKULU PROVINCE OF INDONESIA - Dian Susanti; Aditya Dwi Permana Putra; Devi Safrina; Nur Rahmawati Wijaya; M Bakti Samsu Adi; Rohmat Mujahid; Rizal Maarif Rukmana; Dyah Subositi; Sari Haryanti; Usman Siswanto; Yuli Widiyastuti (BIOTROPIA, 2024)
Article Highlights- This research provides information on the use of medicinal plants for treating malaria among ethnic groups in Bengkulu Province.- This research was part of RISTOJA (Research on Medicinal Plants), national research conducted by the Ministry of Health of the Republic of Indonesia.- Several compounds found in medicinal plants used by traditional healers in the Bengkulu Province have been scientifically proven to be effective as antimalarial medication.AbstractMalaria is a disease with a high mortality rate and is still a significant problem in Indonesia and globally. One of the provinces in Indonesia that uses a diversity of medicinal plants to treat malaria is Bengkulu Province. This research aims to inventory and evaluate the use of medicinal plants as malaria drugs in Bengkulu Province. The research methods used were observation, interviews, and the collection of samples. Respondents were traditional healers from seven ethnic groups in Bengkulu. Plant species, use value (UV) parameters, fidelity level (FL), family use value (FUV), relative frequency of citation (RFC), and plant parts value (PPV) were analyzed. This study found 32 specific herbal concoctions and identified the use of 47 plant species in 28 families used by 20 healers in 6 ethnic groups of Bengkulu. The species Carica papaya, Peronema canescens, and Tinospora crispa have the highest use value, fidelity level, and relative frequency of citation. The Lamiaceae and Caricaceae families have the highest family use value (0.15). The leaves (43.9%) and barks (13.6%) were the most frequently utilized parts of medicinal plants to overcome malaria. Decoction was the method most widely used by traditional healers in Bengkulu to prepare conventional medicine formula.